Ottoman Past and Today's Turkey - Pamuk, Sevket (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This is the first time the continuity of Ottoman culture in contemporary Turkey is discussed by a group of well-known scholars of Ottoman-Turkish history and society. This is done through a series of research essays on Ottoman culture, its organizations, its modes of thought, and its identities (and their changes). Also, they point out the confused view of republican Turks towards their Ottoman past. The insightful essays provide not only original knowledge, but also new interpretations concerning ethnicity and state involvement in identity creation. Furthermore, they give bibliographical information about the views and approaches of the Balkan and Arab scholars towards studying the Ottoman era of their lands. The book should prove indispensable to any scholar or library specializing in Turkish, Ottoman, Islamic and Middle East studies.